Development and Status of the Information Systems / Wirtschaftsinformatik Discipline - An Interpretive Evaluation of Interviews with Renowned Researchers: Part I - Research Objectives and Method - Lange, Carola (2005)
As part of a research project funded by the German Research Foundation (DFG) a series of expert interviews was performed with renowned researchers in the fields of Information Systems (IS) and Wirtschaftsinformatik – the corresponding IS field in German speaking countries. The interviewees selected have been in the field from its beginning and have not only observed the field’s development but have shaped it, for example, through the initiation of conferences and associations, curriculum efforts and by establishing new IS departments. The study’s objective is to reconstruct the development and status of the discipline by taking advantage of the diverse perspectives and experiences of the researchers. This report presents in detail the research approach of the interview study, including the selection of interview partners, the interpretation process, and the topical areas of interview schedule.